2016
DOI: 10.1021/acsomega.6b00040
|View full text |Cite
|
Sign up to set email alerts
|

Well-Dispersed α-Fe2O3Particles for Lead-Free Red Overglaze Enamels through Hydrothermal Treatment

Abstract: The traditional Japanese overglaze ceramic, akae porcelain, typically known for Kakiemon-style wares, has been prized around the world for over 400 years. The red color of akae porcelain provides an attractive contrast to white porcelain. In recent years, because the use of leaded frit in making akae has been restricted by law owing to the effects of lead on human health and the environment, lead-free glass frit mixtures for overglaze ceramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Various studies on the synthesis of new red materials that do not harm the environment continue Red iron oxide (α-Fe 2 O 3 ) pigments have attracted more attention due to their good light fastness, tinting strength, hiding power, durability and low toxicity, and have been widely used in coatings, plastics, ceramics, and other fields. [9,10]. Iron makes up about 6.3% of the Earth's crust; however it is never found in pure form, but instead, combined with other elements, especially oxygen, yielding iron oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on the synthesis of new red materials that do not harm the environment continue Red iron oxide (α-Fe 2 O 3 ) pigments have attracted more attention due to their good light fastness, tinting strength, hiding power, durability and low toxicity, and have been widely used in coatings, plastics, ceramics, and other fields. [9,10]. Iron makes up about 6.3% of the Earth's crust; however it is never found in pure form, but instead, combined with other elements, especially oxygen, yielding iron oxides.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-toxic and safe material for the human body and the environment, it is widely used in different areas other than ceramics, such as resin and paint. Although there are many types of red, such as yellowish and blackish red, the color of α-Fe2O3 is known to vary significantly according to the size and shape of the particles [7][8][9][10][11]. Previous studies have applied different synthesis methods, such as the hydrothermal method, and produced various α-Fe2O3 particles and colors [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many types of red, such as yellowish and blackish red, the color of α-Fe2O3 is known to vary significantly according to the size and shape of the particles [7][8][9][10][11]. Previous studies have applied different synthesis methods, such as the hydrothermal method, and produced various α-Fe2O3 particles and colors [7][8][9][10][11]. Katsuki et al [7,8] demonstrated that α-Fe2O3 nanoparticles display a bright red (vermilion), but they tend to coarsen easily and lose this bright red and become closer to black when sintered by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although the overglaze enamels are depicted by red, green, yellow, blue, purple, and gold colors, they are known as “ akae ,” which means red overglaze enamels, because of difficulties in controlling the red color . We have conducted comprehensive research on lead‐free akae with the aim of controlling its color tone …”
Section: Introductionmentioning
confidence: 99%
“…By focusing on a red pigment mainly comprising α‐Fe 2 O 3 (hematite), microtubule materials composed of silicate‐coated hematite nanoparticles, composite materials of alumina/hematite nanoparticles having high thermal stability with respect to color, and well‐dispersed hematite nanoparticles that are suitable for akae have been synthesized. We also converted a wet‐synthesized Al‐substituted hematite into a commercial reality, and the effects of dispersion and aggregation of the hematite particles on the color tone of powders and red overglaze enamels was clarified .…”
Section: Introductionmentioning
confidence: 99%